2015
DOI: 10.3174/ajnr.a4639
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Prenatal MR Imaging in the Detection of Brain Malformations in Fetuses before the 26th Week of Gestational Age

Abstract: BACKGROUND AND PURPOSE:In several countries, laws and regulations allow abortion for medical reasons within 24 -25 weeks of gestational age. We investigated the diagnostic value of prenatal MR imaging for brain malformations within 25 weeks of gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In addition, postmigratory changes may not yet be present. However, pathological changes that may be associated with ventriculomegaly, such as hemorrhagic residuals at the ependymal, or lissencephaly associated with a dysplastic brainstem or disorders of lamination, respectively, may already be visible before 24 weeks …”
Section: For (Daniela Prayer)mentioning
confidence: 99%
“…In addition, postmigratory changes may not yet be present. However, pathological changes that may be associated with ventriculomegaly, such as hemorrhagic residuals at the ependymal, or lissencephaly associated with a dysplastic brainstem or disorders of lamination, respectively, may already be visible before 24 weeks …”
Section: For (Daniela Prayer)mentioning
confidence: 99%
“…In particular, our study focused on GAs between 20 and 24 weeks because in many countries, crucial decisions such as pregnancy termination are possible only in the early second trimester because of laws and regulations. 2 Until now, most of the MR imaging fetal studies in the literature have referred to normative biometric data published by Parazzini et al in 2008 5 to examine fetuses younger than 24 weeks of gestation. In this study, the authors did not calculate centiles but provided the minimum and maximum of eachmeasuredparameter.…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, imaging is usually performed in the early second trimester (within 24 -25 weeks of gestation) because laws and regulations require crucial decisions to be made within such deadline, and additional MR imaging follow-up is not compatible with time constraints. 2 Prenatal brain MR imaging, in addition to morphologic assessment, relies on biometry evaluation. In particular, linear biometry is a fundamental step in clinical routine practice.…”
mentioning
confidence: 99%
“…In the past two decades, intrauterine MRI (iuMRI) has been widely applied in clinical and research settings. [1][2][3] In particular, the high tissue contrast and multiplanar view of MRI helped to open a new window to important, yet previously neglected, prenatal medicine territories, such as the early development phase of cortical anomalies, acute brain parenchyma injuries (ie, ischaemia), or anomalies of the brainstem. Several studies have reported that iuMRI might provide additional information beyond that of ultrasonography in 5% to more than 40% of cases.…”
Section: Morphology and Function: From Fetal Brain Image To Childhoodmentioning
confidence: 99%